Preparation of novel stable antibacterial nanoparticles using hydroxyethylcellulose and application in paper. (20th January 2016) - Wei, Dafu; Chen, Yan; Zhang, Youwei
Highlights: Novel antibacterial nanoparticles were prepared. The paper coated with the nanoparticles displayed excellent antibacterial activity. The paper coated with the nanoparticles displayed excellent washing durability. Abstract: Taking advantage of the self-assembly between the components, novel stable antibacterial nanoparticles were efficiently fabricated via a facile one-step co-polymerization of acrylic acid (AA) and N, N ′-methylenebisacrylamide (MBA) on a mixed aqueous solution of poly(hexamethylene guanidine hydrochloride) (PHMG) and hydroxyethylcellulose (HEC). The z -average hydrodynamic diameters of the nanoparticles ranged from 220 nm to 450 nm. The inner layer of the nanoparticles is composed of water-insoluble interpolymer complexes of PHMG and PAA networks, while the outer layer is composed of PHMG and HEC. The nanoparticles are stabilized by electrostatic interactions, hydrogen bonding interactions, and the chemical bonds. The nanoparticle solution remained stable in a wide pH range of 2.0–12.0 and at salt concentrations below 0.25 mol/L. The nanoparticles were incorporated into handsheets using a dipping treatment. The resulted handsheets exhibited excellent antimicrobial activities even after multiple water washing treatments. The nanoparticles are promising in fabricating paper, water-based coatings and textiles with permanent antibacterial activity.